Autonomous driving vehicle using arduino and three ultrasonic sensors - Mathe , Rama Krishna; N, A V Rama Krishna Reddy; G, Ashok (The Journal of Multidisciplinary Research, 2021)
Robotics has taken major share in the day to day life of humans. They have enough intelligence, thus covering the maximum area of provided space. Transport industry is one such area where vehicle can drive by its own. An autonomous car is a vehicle capable of sensing its environment and operating without human involvement. A human passenger is not required to take control of the vehicle at any time, nor is a human passenger required to be present in the vehicle at all. An autonomous car can go anywhere a traditional cargoes and do everything that an experienced human driver does. In this paper we are presenting on such implementation of an autonomous obstacle -avoiding robot car using ultrasonic sensor.